Development and Application of Planetary Differential Speed Regulating Device for Feed Water Pump of 350MW Thermal Power Unit - Wang Di Liu Renlong Yang Long (Jixie chuandong)
The necessity of integrated energy-saving reform of boiler feed water pump is explained， the improved scheme of planetary hydraulic speed regulating device is put forward， and its working principle and energy saving characteristic is expounded. Taking a power plant in Xinjiang as an example， the renovation project of feed water pump unit replacing hydraulic coupling with the original size of planetary hydraulic speed regulating device from mechanical system， lubricating oil system and electrical system is carried out. A detailed comparative analysis of the feasibility， economy and effect of the comprehensive energy saving reform of the feed water pump is carried out. It is concluded that the advantages of planetary hydraulic speed regulating device can reduce the power consumption rate of power plant by 0.41%， and at the same time have the characteristics of safety， stability， high efficiency and energy saving.